2017
DOI: 10.1589/jpts.29.716
|View full text |Cite
|
Sign up to set email alerts
|

Discriminative and predictive validity of the short-form activities-specific balance confidence scale for predicting fall of stroke survivors

Abstract: [Purpose] The present study aimed to investigate the discriminative validity of the short-form activities-specific balance confidence scale (ABC scale) in predicting falls, and its validity. [Subjects and Methods] 43 stroke survivors were identified as a group with a history of multiple falls (faller group) and a group without or with a history of one falls (non-faller group). The balance confidence was examined using the ABC scale and the short-form ABC scale. Functional abilities were examined with Fugl-Meye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 29 publications
1
12
0
1
Order By: Relevance
“…To assess the Short ABC-J, the same six items selected in the previous study were used (Peretz, Herman, Hausdorff, and Giladi, 2006), which are as follows: items 5, 6, and 13-16 of the ABC-J, and calculated by dividing the sum of the scores on each question by 6. The total score on the short version of the ABC scale was significantly lower than that on the ABC scale (Schepens, Goldberg, and Wallace, 2010;Wood, Wajda, and Sosnoff, 2019); however, scores were strongly correlated (all rho >0.90) (An et al, 2017;Hewston and Deshpande, 2017;Schepens, Goldberg, and Wallace, 2010), and good psychometric properties have also been found for older adults (Hewston and Deshpande, 2017;Schepens, Goldberg, and Wallace, 2010;Schott, 2014;Skipper and Ellis, 2015), Parkinson's disease (PD) (Cole, Rippey, Naughton, and Silburn, 2016;Franchignoni et al, 2014), multiple sclerosis (MS) (Wood, Wajda, and Sosnoff, 2019), diabetes (Hewston and Deshpande, 2017), and stroke (An et al, 2017).…”
Section: Methodsmentioning
confidence: 85%
See 1 more Smart Citation
“…To assess the Short ABC-J, the same six items selected in the previous study were used (Peretz, Herman, Hausdorff, and Giladi, 2006), which are as follows: items 5, 6, and 13-16 of the ABC-J, and calculated by dividing the sum of the scores on each question by 6. The total score on the short version of the ABC scale was significantly lower than that on the ABC scale (Schepens, Goldberg, and Wallace, 2010;Wood, Wajda, and Sosnoff, 2019); however, scores were strongly correlated (all rho >0.90) (An et al, 2017;Hewston and Deshpande, 2017;Schepens, Goldberg, and Wallace, 2010), and good psychometric properties have also been found for older adults (Hewston and Deshpande, 2017;Schepens, Goldberg, and Wallace, 2010;Schott, 2014;Skipper and Ellis, 2015), Parkinson's disease (PD) (Cole, Rippey, Naughton, and Silburn, 2016;Franchignoni et al, 2014), multiple sclerosis (MS) (Wood, Wajda, and Sosnoff, 2019), diabetes (Hewston and Deshpande, 2017), and stroke (An et al, 2017).…”
Section: Methodsmentioning
confidence: 85%
“…The shortened ABC scale comprised six items that contain relatively high difficult activities (Peretz, Herman, Hausdorff, and Giladi, 2006). It has begun to attract attention, and its psychometric characteristics have been reported in several languages such as English (Cole, Rippey, Naughton, and Silburn, 2016;Hewston and Deshpande, 2017;Schepens, Goldberg, and Wallace, 2010;Skipper and Ellis, 2015;Wood, Wajda, and Sosnoff, 2019), German (Schott, 2014), Italian (Franchignoni et al, 2014), and Korean (An et al, 2017); however, it has not been validated in Japanese. The use of the shortened ABC scale has the following several advantages.…”
Section: Introductionmentioning
confidence: 99%
“…The ABC scale is a valid and reliable tool for prediction of falls. It was shown to be a strong predictor falls for elderly people [ 32 , 33 ], individuals with Parkinson’s disease [ 34 ], post stroke patients [ 35 ], and individuals with multiple sclerosis [ 36 ]. In PPS patients, it was reported that participants (n = 415) who had higher ABC scores were less likely to have risk of falls ( p = 0.028) [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Falls, lowered sense of balance, and depression are not considered serious problems in the elderly as these problems are regarded as simple problems related to aging, and therefore, preventive and therapeutic support to the elderly who reside in the local community is not provided adequately 3 , 4 ) . Rather, such support is provided after the occurrence of falls or depression 5 , 6 ) and it is considered that diversified programs for the elderly residing in the local community should be developed in the future.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, it is necessary to develop an easy and interesting exercise program that reflects features of the elderly rather than an exercise program that is difficult to perform with interest and involves higher cost 7 , 8 ) . Based on this background, in this study, a VR exercise program that is easy to tackle and has an advantage of being utilized as an individualized selection program under safe environment was applied to the elderly with mild depression 6 ) . Through this procedure, we intended to explore the effect of the VR exercise program on physical balance and depression in the elderly 9 ) .…”
Section: Introductionmentioning
confidence: 99%